O BRINCAR E O PROJETO “FAZER EM CANTOS” NA EDUCAÇÃO INFANTIL DO MUNICÍPIO DE ARAÇATUBA-SP - HELOÍSE GRACIELE DE FREITAS FERNANDES (2022)
This paper presents the results of a Master's level research, linked to the line of Education, Childhood and Diversity of the Postgraduate Program in Education at the Federal University of Mato Grosso do Sul - UFMS, Campus Três Lagoas/MS. The object of study was the project "Fazer em Cantos", developed in Araçatuba (SP), with the general objective of getting to know the impacts of the project's execution in Children's Education in the municipal network of Araçatuba-SP. The specific objectives were: retrieve the historical data of the "Fazer em Cantos" Project; describe and discuss the theoretical basis that supported the elaboration of the project; get to know the point of view of the different Project participants (teachers, coordinators and principals) about the project development; discuss the project's contributions to Kindergarten Education in the city of Araçatuba-SP. We started from the understanding that play is the main activity of the childhood period, contributing significantly to the development of children and, as such, needs to be incorporated into the school routine, supported by the Cultural-Historical Theory proposed by Vygotsky. The research, qualitative in nature and with case study characteristics, was developed in the Municipal Education Secretary of Araçatuba/SP and in two of the schools in the municipality where the Project was developed. The first stage of the study was documental in nature and the second empirical, by means of semi-structured interviews, having as subjects some of the Project participants, such as teachers, coordinators and principals. The analysis of the data collected, based on the theoretical conceptions that supported the research, showed that public policies regarding Early Childhood Education must consider children when making their changes in government plans, which implies not abandoning relevant projects, such as the Project in question, and the improvement of existing actions to improve the quality of education. It was concluded that the municipality of Araçatuba/SP should continue the work it already does, investing in the development of proposals that preserve the conception of childhood, in its entirety, and in the strengthening of theoretical bases about playing, pointing out its importance through situations of socialization and games built by the child itself. Keywords: Childhood education; Child development; Play; Main activity or guide activity; "Fazer em Cantos" Project.